Monitoring of quality of essential oil from Etlingera SP. 2 (Zingiberaceae) by GC and GC-MS - Hazrin, Azemi (2008)
Ginger essential oil is highly regarded in the world and has a high commercial value in the world market. There are many types of ginger in the Zingiber family and the one that are studied is a wild species and due to comprehensive morphological examination being carried out by the botanist at Universiti Malaya, the specimen is named Etlingera sp. 2. The main objective of this test is to monitor the quality of its essential oil after being exposed to the heat and light within three weeks period. The specimen essential oil is collected using hydrodistillation process and the compounds of the essential oil are determined using GCMS analysis. The samples are analyzed at the end of every week using the GC method. From the data analysis, the percentage area of three major compounds which is Trans-anethole, p-Anisaldehyde and Camphor are compared to the fresh sample analysis. The analysis due to both test show there are slight changes in the compound percentage area, which is less than 10% meaning that the changes are considered none. The samples from both tests maintain slightly the same properties as the fresh one. From this test, it shows that in the period of three weeks, the changes to the essential oil are minimal and the quality of the essential oil after three weeks is still the same like the freshly extracted.